2023
DOI: 10.1039/d3nj02994h
|View full text |Cite
|
Sign up to set email alerts
|

Spodium, halogen and hydrogen bonds in the reactivity of bis(2,4-bis(trichloromethyl)-1,3,5-triazapentadienato)-Zn(ii)

Ismayil M. Garazade,
Atash V. Gurbanov,
Rosa M. Gomila
et al.

Abstract: The role of noncovalent interactions (spodium, halogen and hydrogen bonds) in the reaction of [Zn{NH=C(CCl3)NC(CCl3)=NH}2] with acetone, pyrazole, 4,4'-bipyridine and Cu(acetylacetonate)2 is reported. Depending on the reactants different types of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The densities at the Sb–N bond critical points are in the range between 0.065 and 0.085. These values clearly exceed the threshold of 0.04 that has been suggested as marking the presence of a coordination bond with dominant covalent character . Note that ρ BCP grows larger for the smaller X substituents.…”
Section: Resultsmentioning
confidence: 66%
“…The densities at the Sb–N bond critical points are in the range between 0.065 and 0.085. These values clearly exceed the threshold of 0.04 that has been suggested as marking the presence of a coordination bond with dominant covalent character . Note that ρ BCP grows larger for the smaller X substituents.…”
Section: Resultsmentioning
confidence: 66%
“…Based on CSD (Cambridge Structural Database) statistical analyses and theoretical calculations, Bauzá et al 16 demonstrated that a σ-hole region exists in the (pseudo)tetrahedral SpX 2 L 2 (Sp = Zn, Cd, and Hg) complexes, which could interact non-covalently with an electron-rich partner. Some tetrahedral and square-pyramidal Zn II complexes, 18–20 such as Zn-porphyrins and aza-crown ethers, are good spodium bonding donors, facilitating the approach of electron-rich atoms. A spodium bond cooperates with other type of noncovalent interactions, assisting metal supramolecular aggregation and networks.…”
Section: Introductionmentioning
confidence: 99%